2012
DOI: 10.1002/bdra.23058
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported maternal smoking during pregnancy by source in Utah, 2003–2007

Abstract: Based on our findings, maternal smoking exposure from interview data was shown to be of higher quality with less misclassification compared to data obtained from medical records or birth certificates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Cervical-vaginal ‘infection’ refers to maternal report of bacterial infection (n = 4), bacterial vaginosis (n = 30), yeast infection (n = 62), mixed infection (n = 4) or other/unspecified infection (n=43; e.g., chlamydia, trichomonas or herpes, etc.). Previous research indicates that such information gained through self-report can be more accurate than that obtained from medical records or birth certificates, 14-17 but we do not know the extent to which ‘infection’ per se was confirmed by microbial colonization. The terms ‘fetal growth restriction’ and ‘small for gestational age’ meet our needs equally, and we use them interchangeably since accurate differentiation of pathologically small from constitutionally small newborns (see 18,19 ) is an ongoing challenge.…”
Section: Methodsmentioning
confidence: 72%
See 1 more Smart Citation
“…Cervical-vaginal ‘infection’ refers to maternal report of bacterial infection (n = 4), bacterial vaginosis (n = 30), yeast infection (n = 62), mixed infection (n = 4) or other/unspecified infection (n=43; e.g., chlamydia, trichomonas or herpes, etc.). Previous research indicates that such information gained through self-report can be more accurate than that obtained from medical records or birth certificates, 14-17 but we do not know the extent to which ‘infection’ per se was confirmed by microbial colonization. The terms ‘fetal growth restriction’ and ‘small for gestational age’ meet our needs equally, and we use them interchangeably since accurate differentiation of pathologically small from constitutionally small newborns (see 18,19 ) is an ongoing challenge.…”
Section: Methodsmentioning
confidence: 72%
“…24,65,66 We do not know the extent to which maternal reported cervical-vaginal infections involved a documented immune response to microbial colonization (i.e., true infection). Previous research indicates that information gained through self-report during maternal interview can be more accurate than that obtained from medical records or birth certificates, 14-17 though modest reliability has also been reported for some obstetric morbidity surveys. 67,68 In the ELGAN Study, newborns whose mother reported a genitourinary infection during pregnancy were more frequently exposed to inflammation of the chorionic plate, chorion, decidua, fetal stem vessels, and umbilical cord than were those whose mother did not.…”
Section: Discussionmentioning
confidence: 99%
“…Steps to improve confidentiality during data collection might result in greater disclosure. In one study on self-reported smoking quality during pregnancy, the use of computer-assisted interviewing technology identified 46.1 % more women compared with the birth certificate [27]. Additional studies are needed to determine whether maternal worksheets can more accurately capture maternal cigarette use before and during pregnancy or if other tools are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Using the clinic data as the gold standard, the sensitivity of maternal report for use of in vitro fertilization (IVF) was 91%. Another validation study compared responses to CATI questionnaire items regarding smoking to data on birth certificates; smoking was more often reported in the NBDPS (Srisukhumbowornchai and others, 2012). Another study conducted a Bayesian bias analysis which incorporated previous research on reliability of self-reported smoking to examine the relationship of smoking and orofacial clefts reported from the NBDPS (Honein and others, 2007; MacLehose and others, 2009).…”
Section: Limitations Of Nbdpsmentioning
confidence: 99%